EFL Students' Speaking Anxiety in Indonesian Senior High School - Marlia Marlia; Fitri Amaliah Akbal; Sahril Nur; Doris McDonald (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2023)
One of the essential abilities in learning English is speaking. However, most students believe that speaking English is challenging because they lack vocabulary and are reluctant to express their opinions. Anxiety is a mood that includes fear, hesitation, and worry about events both in the present and the future. This research aimed to find out the factors causing students’ speaking anxiety, the effects of students’ speaking anxiety, and the students’ strategies to reduce their speaking anxiety. The researchers applied a qualitative research design and used observations and interviews. The population of this study was 90 students in the first grade at SMAN 13 Pangkep Regency, and nine students interviewed by the researchers. The results show that two elements contributed to students’ speaking anxiety: linguistic issues (poor pronunciation, vocabulary, and ideas) and non-linguistic issues (lack of self- confidence, lack of preparation, shyness to their peers, and afraid of being laughed at). Speaking anxiety has two different effects on students’ speaking abilities: a facilitating influence that encourages them to talk and a debilitating effect that causes them to stutter, blank out, become afraid, or stumble. The students' use of preparation, avoidance of eye contact, and peer assistance helps them to reduce their speaking anxiety.